Unstoppable global warming : every 1,500 years - Singer, S. Fred (Rowman & Littlefield Pub. LanhamUS, 2007)
Provides evidence and commentary on the 1,500-year climate cycle. Deals with the flaws of the greenhouse theory and global climate models. Discusses baseless fears and the heavy costs and futility of the Kyoto Protocol.